Recommitting to Marriage on Kate Chopin’s ‘A Respectable Woman’: A Systemic Functional Description - Mentari Putri Pramanenda Sinaga (Journal of English Development, 2022)
A story implies meaning because it is delivered by language. The plot is told by language and the characters in the story are also described by language. The language expresses clauses that can be interpreted. Kate Chopi’s ‘A Respectable Woman’ is a story about a married couple that ends unclear. This story have carried meaning through its ideology. It must be revealed to conclude the story ending. Since this story is not an easy story, Systemic Functional Grammar (SFG) was applied to help the writer exploring the linguistic features. SFG could identify evidences of the story’s meaning. Through qualitative and quantitative methods, the writer presented the description of the Systemic Functional Grammar to present linguistic features and interpret the ideology which is recommitting to marriage.